A 12 week pre-season fitnes training programme for senior male high school rugby players : the effect of supervision on anthropometric, physiological and physical performance variables - Clark, David Rodney (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The study comprises of two sections; i) a survey to determine the attitude towards fitness training for rugby and the current fitness training habits of elite high school rugby players in their penultimate year at school, ii) a training study on a sample of the same population group, to measure the effect of a 12 week fitness training programme, based on scientific principles, on anthropometric, physiological and performance variables. The training study also measured the efficacy of training supervision compared no supervision on these variables.